PROSES KREATIF WAHYU JATMIKO PADA PENCIPTAAN TARI SIMA SWATANTRA ANJUK LADANG - Sugiarti, Yeni; Pramutomo, R.M. (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
This research delves deeply into the creative process undertaken by Wahyu Jatmiko in creating the dance work Sima Swatantra Anjuk Ladang, as well as analyzing the form and presentation of the dance. The main focus of this study is to explore the choreography of Sima Swatantra Anjuk Ladang and to understand how Wahyu Jatmiko's creative process led to the creation of this work. The method used in this research is qualitative with a choreographic approach, which allows the researcher to examine the elements of movement and dance presentation in more detail. To analyze the creative process, the writer applies the 4P theory (Four P’s of Creativity), which includes the aspects of Person (individual), Process, Press (pressure/conditions), and Product. In dissecting the choreography of Sima Swatantra Anjuk Ladang, the writer utilizes key elements of group choreography, such as dance movement, dance space, accompaniment, theme, dance type, as well as supporting elements like costume, lighting, and props. The results of this study show that Sima Swatantra Anjuk Ladang is a representational work that stands out from Wahyu Jatmiko’s other creations. This work was developed through a creative process involving movement exploration, improvisation, and composition, where each stage contributed significantly to the final form of this group dance. Sima Swatantra Anjuk Ladang emerges as a work that not only reflects the creativity of its creator but also embodies rich elements of local aesthetics and culture.